Irish Social Services: a Symposium: the ethical aspect - Coyne, E. J. (Statistical and Social Inquiry Society of Ireland, 1943)
The task allotted to me in this symposium is to consider our Irish Social Services and the Beveridge Report from the ethical point of view. I can only suggest three lines of thought to the members of this Society: suggestions rather than dogmatic assertions. I pick out three moral values for examination and analysis: Liberty, Justice, Brotherliness. These three are actually three of the most specifically human values and possibly the three that most often come in conflict with other values, economic and material ones, for instance.
Symposium on Irish Social Services
Read on Friday, 5th March, 1943
Keywords: Beveridge Report; Ethics; Irish social services; 314.15